Optimization of Management of Agricultural Business Stuctures for Increasing Economic Efficiency - SCUTARI, Sofia; CATAN, Petru; SCUTARI, Oleg (Theoretical and Practical Research in Economic Fields; Vol 16 No 1 (2025): TPREF Volume XVI, Issue 1(33), Spring 2025, 2025)
Agriculture is one of the main sectors of the economy of Ukraine, which provides food security, creates jobs, and promotes the development of rural areas. Changes in the world economy, new technologies, and changes in consumer preferences require agricultural businesses to adapt and improve management approaches. The aim of the article was to create effective approaches to optimizing the management of agricultural businesses to increase their economic efficiency. The research employed financial, statistical, comparative analysis, and SWOT analysis. The results showed that the agricultural sector of Ukraine has great potential for growth but faces a number of challenges. The area of agricultural land in Ukraine (41.5 million hectares) exceeds the area of Germany and France, but the productivity and skill level of workers remain lower. In 2023, the export of agricultural products of Ukraine amounted to € 24 billion, which is significantly inferior to Germany and France. The profitability of agricultural companies of Ukraine was 9.0%, while in Germany it was 12.0%, and in France - 15.5%. This emphasizes the need for more effective management strategies. The need for transition to sustainable agriculture through the implementation of ecological practices that conserve natural resources and ensure food security is determined. The academic novelty of this study is a systematic approach to the analysis and optimization of the management of agricultural businesses in Ukraine. Prospects for future research are the development of management models for agricultural companies that consider the specifics of small and medium-sized enterprises (SMEs), with the aim of increasing their competitiveness.